2020
DOI: 10.1016/j.ymgmr.2020.100645
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the structural impacts of a novel missense variant identified with whole exome sequencing in an Egyptian patient with propionic acidemia

Abstract: Propionic Acidemia (PA) is an inborn error of metabolism caused by variants in the PCCA or PCCB genes, leading to mitochondrial accumulation of propionyl-CoA and its by-products. Here, we report a 2 year-old Egyptian boy with PA who was born to consanguineous parents. Biochemical analysis was performed using tandem mass spectrometry (MS/MS) on the patient's dried blood spots (DBS) followed by urine examination of amino acids using gas chromatography/mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Both genes are linked to inflammation, a process in which multiple pathways interact to contribute to this complex function. The LILRB1 gene is a member of the leukocyte immunoglobulin-like receptor (LILRs; or ILT, LIR, and CD85) family, which are the most conserved genes located within the leukocyte receptor cluster on human chromosome 19 (35,36). The family consists of 13 members with activating or inhibitory properties: LILRs with long cytoplasmic tails that contain inhibitory motifs based on tyrosine act as inhibitory receptors (LILRBs), whereas LILRs with short cytoplasmic tails act as activators (LILRAs).…”
Section: Discussionmentioning
confidence: 99%
“…Both genes are linked to inflammation, a process in which multiple pathways interact to contribute to this complex function. The LILRB1 gene is a member of the leukocyte immunoglobulin-like receptor (LILRs; or ILT, LIR, and CD85) family, which are the most conserved genes located within the leukocyte receptor cluster on human chromosome 19 (35,36). The family consists of 13 members with activating or inhibitory properties: LILRs with long cytoplasmic tails that contain inhibitory motifs based on tyrosine act as inhibitory receptors (LILRBs), whereas LILRs with short cytoplasmic tails act as activators (LILRAs).…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid residue level structural deviation observed with the variant serine (Pro765Ser) in MYO1D is likely to disturb the primary, secondary, tertiary, and quaternary structural features in the protein. Numerous studies have shown the strong correlation between deviations in residue level RMSD score and structural properties for the disease-causing variants (23,(57)(58)(59). Disease causative pathogenic mutations have often changed the energy equilibrium, which is required to maintain the protein stability (60).…”
Section: Discussionmentioning
confidence: 99%
“…Tandem mass spectrometry (MS/MS) was performed on the patient's dried blood spots, revealing an elevated C3‐carnitine and C3‐/C2‐carnitine ratio, whilst urinary amino acids were evaluated using gas chromatography/mass spectrometry (GC/MS), which demonstrated increased excretion of methyl citrate and 3‐hydroxy‐propionate. The patient's metabolomic profiles, together with in silico modelling of the c.1427G>C p.(Arg476Pro) PCCA variant, facilitated its classification as ‘likely pathogenic’, thereby confirming the diagnosis [ 97 ].…”
Section: Mitochondrial Metabolomicsmentioning
confidence: 99%